2018
DOI: 10.1159/000494933
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Methods for the Investigation of Cell Contact Dynamics in Endothelial Cells Using Florescence-Based Live Cell Imaging

Abstract: Endothelial cells of the vascular system are dynamic cells whose molecular adaptability is decisive for the adjustment of homeostasis and organ perfusion. Advanced microscopic techniques, automation processing, and image analysis software was shown to improve the understanding of vascular biology. In this work, we describe advanced methods that allow investigating the dynamics of endothelial cell contacts. The development of viral vectors has contributed significantly to the genetic manipulation of endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…There is EPLIN-a, which consists of 600 amino acids and a larger EPLIN-b isoform with 759 amino acids (Chen et al, 2000). Previous work on EPLIN in ECs demonstrated that both EPLIN isoforms localize as components of the JAAF, while EPLIN-a was additionally found at JAIL (Hofer et al, 2018), which is in agreement with its impact on angiogenesis (Chervin-Pé tinot et al, Sanders et al, 2010).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…There is EPLIN-a, which consists of 600 amino acids and a larger EPLIN-b isoform with 759 amino acids (Chen et al, 2000). Previous work on EPLIN in ECs demonstrated that both EPLIN isoforms localize as components of the JAAF, while EPLIN-a was additionally found at JAIL (Hofer et al, 2018), which is in agreement with its impact on angiogenesis (Chervin-Pé tinot et al, Sanders et al, 2010).…”
Section: Introductionsupporting
confidence: 54%
“…Cell migration and cell junction dynamics directly relate to formation of Arp2/3 complex-dependent plasma membrane protrusions including cLP and JAIL, respectively (for review, see Cao and Schnittler, 2019;Krause and Gautreau, 2014). Since EPLIN interferes with Arp2/3 complex function (Maul et al, 2003) and that EPLIN-a localizes at JAIL and cLP (Hofer et al, 2018), we investigated whether EPLIN isoform expression correlates with cell density in HUVEC cultures. Indeed, subconfluent EC cultures (3À4 3 10 4 cells/cm 2 ) expressed about 2 times more EPLIN-a than confluent cultures (0.9À1.2 3 10 5 cells/ cm 2 ), while EPLIN-b expression remained unchanged (Figure 1C).…”
Section: Eplin-a Expression Increases In Growing Ecsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underlying cell junction remodeling involve actin-and myosinmediated contractility, tyrosine phosphorylation of VE-cadherin, p120 ctn -mediated endocytosis and the formation of actin-driven plasma membrane protrusions (Doggett and Breslin, 2011; Hoelzle and Svitkina, 2012;Martinelli et al, 2013;Adderley et al, 2015). In addition, live-cell imaging is being increasingly used (Day and Davidson, 2009;Frigault et al, 2009;Cranfill et al, 2016;Seebach et al, 2016;Hofer et al, 2018), as it allows the direct observations of junction remodeling with high spatial and temporal resolution, thus providing valuable hints regarding the underlying mechanisms. In this context, our laboratory has focused on the interdependency between actin-driven membrane protrusions and VE-cadherin-mediated adhesion.…”
Section: Introductionmentioning
confidence: 99%